Untapped Talent in Public Administrations : How can we identify, measure, and combine talents to form the strongest project teams within the public administration? - TOKO KOUTOGUI, Abdoul kafid (My University, 2022)
The implications of cognitive diversity were analysed in this study based on Sternberg's theory of multiple intelligences. We measured creativity, emotional intelligence, practical intelligence and practical intelligence in a sample (N=46) of individuals. The innovative capacity of individuals was identified by testing their ability to propose innovative ( novel, useful, and feasible) solutions to complex societal problems. Creativity and practical intelligence were identified as key attributes that promote people's innovation. Through clustering using the K-means method, we were able to determine two types of groups of people (the innovative and the less innovative) who differ in their creativity and practical intelligence style. Through this study we were also able to demonstrate that the parameters novelty, feasibility, and utility are variables that can contribute to the creation of an innovation indicator.
Keywords: innovation; SOCIAL SCIENCES::Social sciences::Psychology::Cognitive science; SOCIAL SCIENCES::Other social sciences::Public sector research; intelligence